IMPLEMENTASI PROGRESSIVE WEB APPLICATION PADA WEBSITE FRIZFOO MENGGUNAKAN EXPRESS.JS - Karli, Theodorus; Muawwal, Ahyar; Thayf, Mohammad Sofyan S (KHARISMA Tech, 2023)
The aim of this study is to implement Progressive Web Apps (PWA) technology on the Frizfoo website using the Express.js framework so that it can be accessed in the form of native applications via the user’s smartphone home screen and can be run offline. The implementation of PWA as one of the “should have” features aims to provide added value and improve website performance, as well as overcomes website limitations in displaying offline pages, and avoid the cost of developing native applications on various operating systems platforms. Data collection methods involve literature study and direct measurement using several tools. Testing included installable testing, PWA criteria, performance, size transferred resources, and offline mode. Components used in PWA include web app manifest, service worker, and cache storage. PWA implementation involves creating a web app manifest, service worker registration file, configuring service worker files, adding script tags, creating custom routes in Express.js, and testing PWA. The test results show that the Frizfoo website can be installed and used properly on various types of mobile devices. PWA was successfully implemented and met all PWA criteria, by getting a total score of 10 on Lighthouse and a total score of 25 on PWABuilder. The results of performance testing on Lighthouse and GTMetrix have increased by 36% after the implementation of PWA. The size of transferred resources has reduced from 3.1 MB to 1.8 MB and the website load time has decreased from 3.65 seconds to 826 ms so that the website can be loaded faster. And offline mode feature of the Frizfoo website is successfully used in offline conditions or with an unstable internet connection.